Synthesis and Study The Dielectric Properties of La-Doped and Undoped Barium Titanate Nanopowders - Sabah M. Ali Ridha; Mojahid Mohammed Najim (Engineering and Technology Journal, 2015)
Lanthanum doped Ba1-xLaxTiO3 (BLT) with ( x = 0.005, 0.015, 0.02, 0.025) and undoped Barium titanate BaTiO3 (BT) nanopowders were synthesized at Room temperature via a semi-oxalate method with adjusting a pH of the solution around (5.5).Crystallization processes and Particles size of prepared powders were studied, measured and calculated by using X-ray diffraction. XRD analysis and Scanning Electron Microscopy SEM techniques, and the particles size was found to be about 65 nm. The dielectric properties (real є' and imaginary є" part of dielectric constant) of polymer/BT, polymer/BLT nanocomposites, and UPE (unsaturated polyester resin) samples were studied at different frequencies in the range of (20kHz-5MHz) using LCR meter, while theoretical dielectric constant of the prepared samples were calculated by using Bruggeman rule of mixture. The results of dielectric measurements found that the real dielectric constant and tangent loss of the nanocomposites samples decreases with increasing Lanthanum content.